Cost-minimisation analysis versus cost-effectiveness analysis, revisited. - Dakin, H; Wordsworth, S (2013)
We aim to establish whether it is ever appropriate to conduct cost-minimisation analysis (CMA) rather than cost-effectiveness analysis.We perform a literature review to examine how the use of CMA has changed since Briggs and O'Brien announced its death in 2001. Examples of simulated and trial data are presented: firstly to illustrate the advantages and disadvantages of CMA in the context of non-inferiority trials and those finding no significant difference in efficacy and secondly to assess whether CMA gives biased results.We show that CMA is still used and will bias measures of uncertainty, causing overestimation or underestimation of the value of information and the probability that treatment is cost-effective. Although bias will be negligible for non-inferiority studies comparing treatments that differ enormously in cost, it is generally necessary to collect and analyse data on costs and efficacy (including utilities) to assess this bias. Cost-effectiveness analysis (including evaluation of the joint distribution of costs and benefits) is almost always required to avoid biased estimation of uncertainty. The remit of CMA in trial-based economic evaluation is therefore even narrower than previously thought, suggesting that CMA is not only dead but should also be buried.